Ibn Sina's Thoughts on Education and Their Relevance to Contemporary Islamic Education - Saripudin; Maragustam (LECTURES: Journal of Islamic and Education Studies, 2024)
Education aims to improve the quality of human resources through various learning processes. Ibn Sina (Avicenna) was a famous Islamic philosopher in the field of medical science, but many of his thoughts also discussed education and are considered to have made a major contribution to the development of contemporary Islamic educational thought. Compiled from various reference sources obtained, Ibn Sina's educational concept discusses, among other things, the aims of Islamic education, the curriculum in first level education units, how to become an educator, provisions for being a student and the learning environment. This thinking can be the basis for the development of contemporary education, especially as a philosophical basis for designing a good but still adaptive education system. The aim of this research is to discuss Ibn Sina's educational thoughts and his contribution to contemporary Islamic education. The research method used in this research is the library research (library research) method. The results of this study provide an illustration that Islamic education according to Ibn Sina includes dimensions of educational goals, nature of education, curriculum, dimensions of educational methods, dimensions of educators, dimensions of students.